Thrombin stimulates gene expression and secretion of IL-11 via protease-activated receptor-1 and regulates extravillous trophoblast cell migration. (April 2019) - Brünnert, Daniela; Shekhawat, Indu; Chahar, Kirti Raj; Ehrhardt, Jens; Pandey, Janmejay; Yadav, Jay Kant; Zygmunt, Marek; Goyal, Pankaj
Highlights: Thrombin stimulates IL-11 expression and secretion in extra villous trophoblast. Activation of thrombin receptor PAR-1 regulates IL-11 expression and secretion. Thrombin enhanced the cell migration in IL-11 dependent manner. Abstract: Extravillous trophoblast (EVT) migration and invasion is the crucial step for normal placental development. IL-11 is a cytokine regulating cell migration and invasion in cells and is a critical factor for successful implantation of an embryo. Higher expression of thrombin receptor PAR-1 was reported in early pregnancy. The precise role of thrombin in trophoblast functions is not well understood. In this study, we asked whether thrombin can induce IL-11 secretion in trophoblasts if yes, which physiological cell functions are possibly affected? In this study, HTR-8/SVneo cells, which were originally derived from first-trimester villous explants of early pregnancy were used as the extravillous trophoblast (EVT) model. BeWo cells were used as the cytotrophoblast model. For gene silencing, qPCR and ELISA, each experiment was performed in triplicates for minimum three times. Here, we found that thrombin stimulates IL-11 gene expression and protein secretion in HTR-8/SVneo cells but not in BeWo cells. PAR-1 was the only receptor which was highly expressed in HTR-8/SVneo cells. Thrombin-mediated expression and secretion of IL-11 were mainly activated via PAR-1 receptor. Rac1, but not Rho-kinase activation is required for thrombin-induced IL-11 secretion. We also found that thrombin stimulation significantly enhanced cell migration that was inhibited after silencing the IL-11 gene. In conclusion, this study demonstrates the role of thrombin in regulating human EVT migration via IL-11 secretion. We propose that thrombin might regulate EVT migration through the decidua and spiral artery remodeling. Failure of thrombin-dependent EVT migration results in pregnancy disorder, such as preeclampsia.